2017
DOI: 10.1038/s41598-017-04772-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between allergic conditions and colorectal cancer risk/mortality: a meta-analysis of prospective studies

Abstract: We aimed to assess the association between allergic conditions and risk/mortality of colorectal cancer (CRC). A systematic literature search was conducted using Pubmed and Embase to identify relevant studies. Prospective studies assessing the association between allergic conditions and risk/mortality of CRC were included. Risk ratios (RRs) were pooled with either a fixed- or a random-effects model according to heterogeneity. A total of 515379 participants and 10345 CRC cases from 12 studies were included in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 38 publications
(46 reference statements)
3
10
0
2
Order By: Relevance
“…This result was supported by Ma et al 19 who concluded that there is an inverse association between allergic conditions on the one side and colorectal cancer on the other side. Also, Kozłowska et al 20 found that patients with cancer had a slightly but significantly lower risk of IgE-mediated allergic diseases than those in the control population.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…This result was supported by Ma et al 19 who concluded that there is an inverse association between allergic conditions on the one side and colorectal cancer on the other side. Also, Kozłowska et al 20 found that patients with cancer had a slightly but significantly lower risk of IgE-mediated allergic diseases than those in the control population.…”
Section: Discussionsupporting
confidence: 53%
“…Mean±SD (49.12±13. 19). There was no statistical significance difference between the two studied groups in age or gender distribution.…”
Section: Demographic Data Of the Included Individualsmentioning
confidence: 99%
“…Allergic conditions have been associated with reduced risks of certain cancers [ 81 ]; however, the association with CRC remains inconsistent [ 82 84 ]. Our study found an association between history of allergy/asthma, especially earlier age at onset (and hence longer duration since onset), and reduced EO-CRC risk.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, eosinophils elicited a potent anti-tumor response that was unconnected with CD8 + cells [ 152 ]. The existence of a negative correlation between allergy and CRC risk and mortality has been described [ 153 , 154 , 155 ], however, specifically in the case of food allergy, there is not enough evidence to support this link with CRC [ 156 ]. The presence of eosinophils in the blood is a hallmark of allergic diseases and a negative correlation was described between blood eosinophil counts and CRC risk [ 157 ].…”
Section: Type 2 Immune Cells In Crcmentioning
confidence: 99%